DESAIN PELAT BETON BERPORI DENGAN POLIKARBONAT - Nurtanto, Dwi; Hasanuddin, Akhmad (FSTPT Indonesia, 2015)
Porous concrete which became one of the solutions in pavement construction and is a product that can be said to be successful in meeting the expectations as environmentally friendly construction. Polycarbonate is a thermoplastic polymer group, is formed by applying heat. This type of plastic is used widely in the chemical industry today. Plastic has many advantages, namely thermal resistance compared with other types of plastic, resistant to impact, and very clear. Research